Speckle Tracking Analysis of Left Ventricular Systolic Function Following Traumatic Brain Injury: A Pilot Prospective Observational Cohort Study. Issue 2 (April 2020) - Krishnamoorthy, Vijay; Chaikittisilpa, Nophanan; Lee, James; Mackensen, G. Burkhard; Gibbons, Edward F.; Laskowitz, Daniel; Hernandez, Adrian; Velazquez, Eric; Lele, Abhijit V.; Vavilala, Monica S.
Abstract : Background: Systolic dysfunction and reduction in left ventricular ejection fraction (LVEF) has been documented after traumatic brain injury (TBI). Speckle tracking is an emerging technology for myocardial strain assessment which has been utilized to identify subclinical myocardial dysfunction, and is most commonly reported as global longitudinal strain (GLS). We examined myocardial strain and regional strain patterns following moderate-severe TBI. Materials and Methods: We conducted a prospective cohort study of moderate-severe TBI patients (Glasgow Coma Scale⩽12) and age/sex-matched controls. Transthoracic echocardiography was performed within the first day and 1 week following TBI. Myocardial function was assessed using both GLS and LVEF, and impaired systolic function was defined as GLS >−16% or LVEF ⩽50%. Regional strain patterns and individual strain trajectories were examined. Results: Thirty subjects were included, 15 patients with TBI and 15 age/sex-matched controls. Among patients with adequate echocardiographic windows, systolic dysfunction was observed in 2 (17%) patients using LVEF and 5 (38%) patients using GLS within the first day after TBI. Mean GLS was impaired in patients with TBI compared with controls (−16.4±3.8% vs. −20.7±1.8%, P =0.001). Regional myocardial examination revealed impaired strain primarily in the basal and mid-ventricular segments. There was no improvement in GLS from day 1 to day 7 ( P =0.81). Conclusions: Myocardial strain abnormalities are common and persist for at least 1 week following moderate-severe TBI. Speckle tracking may be useful for the early diagnosis and monitoring of systolic dysfunction following TBI. Abstract : Supplemental Digital Content is available in the text.